Penerapan Strategi Mind Mapping dalam Meningkatkan Pemahaman Siswa pada Pembelajaran Sejarah Bani Umayyah di MAS Al-Washliyah P. Berandan - Zulfi Ayuni, Zulfi; Rasyid, Muhammad Nuh (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2023)
The research in based on the results of observations of students in class XI MAS Al-Washliyah P. Berandan, it was found that the daily grades of Islamic Cultural History subjects in class XI MAS Al-Washliyah were on average still low or under the KKM (Minimum Completeness Criteria).The shows that most students do not understand the material being taught so that if affects learning outcomes. The purpose of this study is to find out the application of mind mapping strategies in improving students' understanding, especially in the Umayyad History lesson. The research sample is class XI Religion students, totaling 24 people. The type of research used is quantitative research with experimental methods with One Grup Pretest Posttest Design. Data collection techniques in this study were using observasion, tests, and documentation. The result showed that the application of mind mapping strategies could improve students' understanding. Students' understanding before (pretest) applied mind mapping strategy was 51,25 after being implemented with mind mapping strategy (posttest) was 81,88. Meanwhile, for the results of hypothesis testing, a value of 0,00 is obtained, this indicates that there is an effect of applying mind mapping strategies in increasing students' understanding of the history of rhe Umayyads.